A Portable Spectropolarimeter for Field Crop Canopies: Distinguishing species and cultivars of fully developed canopies by polarized light - Michio Shibayama; Shigeo Akita (Plant Production Science, 2002)
A spectropolarimeter equipped with eight spectral bands in the visible, near– and short–wave infrared ranges (490–2200 nm) as well as a rotary film polarizer has been developed for measuring the reflectance and degree of polarization of light reflected from field crop canopies. This paper describes the design and specification of the instrument and the results of preliminary field experiments. Solar and view zenith angles and view azimuth direction relative to the solar position had a much greater influence on polarization than reflectance. For fully developed sweet potato and soybean canopies, the degree of polarization was a better discriminator of the canopy than each single band reflectance and a reflectance–based vegetation index such as normalized difference vegetation index (NDVI).